So B. It : [compact disc, unabridged] : a novel - Weeks, Sarah (Harper Children's Audio, 2004)
After spending her life with her mentally retarded mother and agoraphobic neighbor, twelve-year-old Heidi sets out from Reno, Nevada, to New York to find out who she is.